Avaliação da política de inclusão de pessoas com surdez no mercado de trabalho no município de Maracanaú (Ceará) - Araújo, Suzana Leite de (2024)
The inclusion policy for people with disabilities (PcD) in the labor market is based on the Quota Law, enacted in the early 1990s, and many studies demonstrate that this inclusion instrument has proven to be insufficient and ineffective and there is great variability in its implementation in the country (Santos; Vieira; Faria, 2013; Albuquerque; Borges; Mendes, 2018; Loxe et al., 2019). Considering the above, the objective was to evaluate in depth (Rodrigues, 2008) the public policy for the inclusion of people with deafness in the job market in the municipality of Maracanaú–Ceará, Brazil, considering that the community of people with deafness faces several challenges in terms of communication and placing yourself in the world of work. Firstly, the legislation that defines the policy was analyzed, based on documents and a survey was carried out with SINE-IDT of data on people with deafness in the Maracanaú labor market. Interviews were carried out using semi-structured questionnaires with an IDT-SINE-CE Coordinator and four deaf people, with the help of a LIBRAS interpreter, seeking to identify differences in the perception of these groups. A qualitative and descriptive approach was used to interpret phenomena and attribute meanings (Gil, 2008). The analysis of these data occurred based on discourse analysis (Orlandi, 2009). We sought to understand the public policy for the inclusion of people with deafness in companies, based on the perception of the manager and people with deafness. The existence of a consistent job offer, largely associated with the Industrial District of Maracanaú, and the action of IDT/SINE-CE and SINE Municipal, place Maracanaú ahead of most municipalities in Ceará, in terms of insertion of people with disability in the labor market. Current data (February 2024) show that there are around 2,247 PcD employed in private companies in Maracanaú, with the deaf community representing 15.9% of this value, that is, around 357 employees. The numbers, however, are much lower than they could be if the Quota Law were complied with in its entirety. In general, the deaf people interviewed said they knew the Quota Law superficially, although they recognized the importance of this public policy. They believe that the Quota Law needs to be more publicized, and that the percentage of vacancies should be increased and that more opportunities should be given to people with deafness and other types of disabilities. The lack of knowledge of LIBRAS in companies is the determining factor that makes communication difficult and harms the performance of deaf workers. Also noteworthy is the total or partial absence of good visual communication and sound alarms, as well as the lack of support from private companies for the continued training of people with deafness. In general, the analysis of the speeches of deaf workers made it possible to identify different ways of thinking and acting of people with deafness, in relation to legislation and the reality of the world of work around them. Based on what was exposed in this work, recommendations were presented to promote greater integration of public institutions and expand actions that favor the inclusion of people with deafness in society and the job market.